1989
DOI: 10.1111/j.2042-7158.1989.tb06451.x
|View full text |Cite
|
Sign up to set email alerts
|

The availability of diltiazem: A study on the sorption by intravenous delivery systems and on the stability of the drug

Abstract: The stability and the sorption by intravenous delivery systems of the calcium antagonist diltiazem dissolved into either 5% dextrose or 0.9% sodium chloride solutions have been investigated, under conditions simulating current clinical practice. Static experiments showed an excellent stability and no sorption after 48 h. Dynamic experiments, at a perfusion rate of 20 mg h-1, showed no sorption of the drug by infusion fluid containers, burettes or administration sets. For end-line filters a temporary decrease o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…5 Per the manufacturer, diltiazem hydrochloride 1-mg/mL injection is physically compatible and chemically stable in polyvinylchloride bags when stored at room temperature or under refrigeration for 24 hours in 5% dextrose injection, 0.9% sodium chloride injection, or 5% dextrose and 0.45% sodium chloride injections. 6 De Vroe et al 5 found that when diluted in 5% dextrose injection or 0.9% sodium chloride injection, diltiazem was stable for 48 hours when stored at room temperature. However, no stabilityindicating study has evaluated the stability of diltiazem infusions when stored for 30 days at various temperatures.…”
mentioning
confidence: 99%
“…5 Per the manufacturer, diltiazem hydrochloride 1-mg/mL injection is physically compatible and chemically stable in polyvinylchloride bags when stored at room temperature or under refrigeration for 24 hours in 5% dextrose injection, 0.9% sodium chloride injection, or 5% dextrose and 0.45% sodium chloride injections. 6 De Vroe et al 5 found that when diluted in 5% dextrose injection or 0.9% sodium chloride injection, diltiazem was stable for 48 hours when stored at room temperature. However, no stabilityindicating study has evaluated the stability of diltiazem infusions when stored for 30 days at various temperatures.…”
mentioning
confidence: 99%